EVALUASI KEBIJAKAN BUPATI KUKAR NOMOR 6 TAHUN 2011 TENTANG PELIMPAHAN SEBAGIAN KEWENANGAN BUPATI KEPADA CAMAT (STUDI KASUS KECAMATAN SAMBOJA) - Fahmi . (Jurnal Paradigma (JP), 2017)
This article is an effort to evaluate the authority transformation policy from Bupati to Camat based on UU No. 32 year 2004. Its purpose is to increase the quality and effectivity of public services. Implementing of this policy needs the society consciousness and government commitment. Then, the coordination between institutions within the government is nessecary to endorse the implementation of Bupati Policy Number 6 year 2011 concerning to the authority transformation.